2001
DOI: 10.1111/j.1572-0241.2001.03794.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal Papillary-Mucinous Tumors of the Pancreas: Differential Diagnosis Between Benign and Malignant Tumors by Endoscopic Ultrasonography

Abstract: Main duct type tumors with > or =10 mm dilated MPD, branch duct type tumors (>40 mm) with irregular septa, and large mural nodules (>10 mm) strongly suggest malignancy on EUS. EUS would be a useful modality for differentiating between benign and malignant IPMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(50 citation statements)
references
References 26 publications
2
46
0
2
Order By: Relevance
“…The imaging diagnosis of BD-IPMN is usually made using CT and MRCP in combination with EUS or ERCP [10,11,16,17,18]. EUS is an especially accurate tool for differentiating BD-IPMN lesions from other cystic pancreatic lesions; EUS has a 92% diagnostic accuracy and permits adequate diagnosis of the presence, size, and extent of BD-IPMN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imaging diagnosis of BD-IPMN is usually made using CT and MRCP in combination with EUS or ERCP [10,11,16,17,18]. EUS is an especially accurate tool for differentiating BD-IPMN lesions from other cystic pancreatic lesions; EUS has a 92% diagnostic accuracy and permits adequate diagnosis of the presence, size, and extent of BD-IPMN.…”
Section: Discussionmentioning
confidence: 99%
“…BD-IPMNs were diagnosed based on the pathognomonic findings of ERP, i.e. a dilated cyst greater than 10 mm in diameter [6], communication between the cyst and the main pancreatic duct (MPD), and the presence of mucin, as indicated by filling defects in the pancreatic duct [16,17]. Patients who did not undergo ERP were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 That is, in comparison to tumor involving the branches, tumor involving the main duct is usually associated with greater progression of histological features. Kubo et al 9 showed the diameters of the dilated ducts to be significant in the diagnosis of IPMT. They showed both a main pancreatic duct tumor with the duct dilated to 10mm or more in diameter and a branch pancreatic duct tumor (Ͼ40 mm) with irregular thick septa to be associated with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Die EUS hat in erfahrenen Händen eine hohe Bedeutung, da sie im Vergleich zu den Schnittbildverfahren eine höhere räumliche Auflösung bietet und auch als sensitiver im Nachweis muraler Knoten gilt [13]. Der entscheidende Vorteil liegt in der Möglichkeit, Feinnadelaspirationen vorzunehmen und das gewonnene Material zytologisch zu untersuchen, die Konzentration von Tumormarkern zu bestimmen oder molekulare Untersuchungen vorzunehmen [3].…”
Section: Welche Bildgebungunclassified